Semen Characteristics, Testicular Size, and Reproductive Hormone Concentrations in Mature Duroc, Meishan, Fengjing, and Minzhu Boars - Borg, K.E.; Lunstra, D.D.; Chiristenson, R.K. (Oxford University Press, 1993)
Chinese breeds of swine are known for their reproductive prolificacy and are noted for large litter size. The current investigation evaluated reproductive components of three breeds of Chinese boars in comparison to a contemporary sire breed common in the U.S. Semen from postpubertal Duroc, Meishan, Fengjing, and Minzhu boars was collected during four seasons of the year. After each semen collection and evaluation period, boars were weighed and placed in a restraining chute for testicular measurements and blood sampling for measurement of FSH, testosterone, and inhibin. Although Duroc boars were 2 mo younger than Chinese boars, initial and final body weight and paired testis volume in Durocs were greater (p < 0.05) than in Chinese boars. Total spermatozoa per ejaculate was similar for Duroc and Minzhu boars, but was lower (p < 0.05) in Fengjing and Meishan boars. Progressive motility and sperm morphological characteristics were not affected by breed of boar. Serum FSH concentrations were markedly higher (p < 0.01) in Meishan and Fengjing boars than in other breeds, and concentrations were nearly 8-fold higher in Meishan than in Duroc boars. Breed differences in serum inhibin were essentially the inverse of those observed for FSH, with Durocs exhibiting the highest inhibin concentrations and Meishans exhibiting the lowest. Testosterone values were not different between breeds. However, testosterone concentrations fluctuated with season, and serum testosterone was highest during the fall of the year in all breeds. These results indicated that some reproductive characteristics differ dramatically between Duroc and Chinese breeds of boars. Breed differences existed in body size, testis size, sperm per ejaculate, ejaculate volume, and serum FSH and inhibin concentrations. However, similarities among breeds in sperm motility and morphology, and in testosterone concentrations indicated that some reproductive characteristics in boars have been conserved through thousands of years of selection.